Ad Intrusiveness dan Sikap Konsumen terhadap Iklan On-Line pada E-Commerce - Wahyu Raharjo; Widyastuti Widyastuti (BISMA (Bisnis dan Manajemen), 2019)
There are lots of online advertisements presented by E-commerce, but online advertising in the form of remarketing is the most intrusive advertisement. Remarketing ad is included as an ad intrusiveness which is very disturbing and can build a negative attitude towards ad, and it will make a negative purchase intention too. But in reality, this advertisement is very developed and almost E-commerces implement it, while what happens is that many consumers actually feel annoyed. The purpose of this study is to analyze and discuss the effect of ad intrusiveness in the form of remarketing toward purchase intention of E-commerce with an attitude toward ad as an intervening variable. The sampling technique used is non-probability sampling with judgmental sampling method. The sample used was 220 respondents. Respondents in this study were E-commerce users aged 19 and above who had seen ad intrusiveness in the form of remarketing. Questionnaire uses likert scale and  processing using path analysis. The results show that ad intrusiveness has a negative and significant effect on attitude toward ad and attitude toward ad has a positif and significant effect ad toward purchase intention.